Macrocyclic oligomers as compatibilizing agent for hemp fibres/biodegradable polyester eco-composites. (20th June 2018) - Conzatti, Lucia; Brunengo, Elisabetta; Utzeri, Roberto; Castellano, Maila; Hodge, Philip; Stagnaro, Paola
Abstract: Ring:chain equilibria (RCE), existing under appropriate reaction conditions, between a linear polyester and the corresponding family of macrocyclic oligomers (MCOs), were exploited to develop an original compatibilizing pathway for preparing eco-composites based on hemp fibres and a biodegradable random co-polyester, namely poly(1, 4-butylene adipate- co -terephthalate) (PBAT) with 50:50 adipate:therephthalate proportion. Cyclo-depolymerization (CDP) of PBAT was successfully carried out at high dilution using various solvents, catalysts, and reaction times. The reconversion of MCOs into linear chains by entropically-driven ring-opening polymerization (ED-ROP) occurs by simple heating in the bulk. This reaction, after optimization of catalyst amount, temperature, and reaction time, was used for the surface modification of hemp fibres. PBAT-based eco-composites containing hemp fibres as such or pre-modified by treatment with the MCOs were then prepared and characterized by morphological, mechanical and dynamic-mechanical analysis. Graphical abstract: Image 1 Highlights: Macrocyclic oligomers (MCOs) easily obtained by cyclo-depolymerization of PBAT polyester. The MCOs easily underwent entropically driven ring opening polymerization (ED-ROP). Low cost hemp fibres efficiently modified with the MCOs via ED-ROP. Good fibre/matrix adhesion in PBAT composites containing MCO-modified hemp fibres. Good mechanical performance of the PBAT/modified hemp fibres biodegradable eco-composites.